Nanometer copper film for packaging interconnection and preparation method and application thereof
Patent Information
- Application Number
- CN202410542776.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-30
AI Technical Summary
[0003]本发明提供一种封装互连用纳米铜膜及其制备方法、应用,用于克服现有技术中银膜强度差,转移工艺复杂,成本高等缺陷
[0028](1)成本优势:原材料成本低,纳米银原材料成本约为纳米铜的15~30倍;铜纳米线制备及洗涤成本低,采用耐压瓶等可耐高压耐温密封容器,在敞口油浴锅中即可制备,反应过程可实时监控,且铜纳米线在长度上为微米级,产量高,洗涤简单,且铜纳米线洗涤不需使用单一高成本的溶剂,而是采用少量多种酸碱溶液和有机溶剂、去离子水间复配来去除铜纳米线表面的包覆物。
Smart Images

Figure CN118422195B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal nanomaterials and power electronic packaging technology, and in particular to a nano-copper film for packaging interconnection, its preparation method, and its application. Background Technology
[0002] In power electronic modules (IGBT modules, rectifier modules), with the increasing operating voltage and current, the requirements for the thermal conductivity, operating temperature, and reliability of the interface layer are becoming increasingly stringent, with operating temperatures exceeding 200℃. Currently, the market primarily uses silver nanoparticles to fabricate silver films for interconnecting modules and substrates. However, these silver films have poor strength, and the transfer process is complex, requiring specialized equipment. Furthermore, the high cost of silver limits the large-scale use of silver nanoparticle paste or silver films. Copper, on the other hand, possesses similar properties to silver but at a significantly lower cost. Therefore, using copper nanowires to fabricate copper films shows great potential as a replacement for silver nanoparticle films. Summary of the Invention
[0003] This invention provides a nano-copper film for encapsulation interconnection, its preparation method, and its application, which overcomes the shortcomings of existing silver films such as poor strength, complex transfer process, and high cost.
[0004] To achieve the above objectives, this invention proposes a method for preparing a nano-copper film for encapsulation interconnection, comprising the following steps:
[0005] S1: Add copper source, surface coating agent, reducing agent, and deionized water to a high-pressure and high-temperature resistant sealed container. The molar ratio of copper source, surface coating agent, and reducing agent is 1:(2-10):(0.2-5). Stir in an oil bath at 60-120°C until a uniform blue suspension is formed. Turn off the stirring, then raise the oil bath temperature to 120-180°C and react at 120-180°C for 3-10 hours. When the reaction solution turns reddish-brown, turn off the heating and cool to room temperature to obtain copper nanowire mother liquor.
[0006] S2: Add solvent and stir at 40-80℃ for 0.1-1h to obtain copper nanowire dilution solution;
[0007] S3: The copper nanowire dilution solution is added to the papermaking equipment. After solid-liquid separation under positive and negative pressure, the mixture is rinsed and then vacuum dried to obtain a copper nanofilm.
[0008] To achieve the above objectives, the present invention also proposes a nano-copper film for encapsulation and interconnection, which is prepared by the preparation method described above; the nano-copper film has a thickness of 20–300 μm and an areal density of 40–500 g / m³. 2 The impurity content is less than 1%.
[0009] To achieve the above objectives, the present invention also proposes an application of a nano-copper film for packaging interconnects, wherein the nano-copper film prepared by the above-described preparation method or the above-described nano-copper film is used as a thermal interface material in the field of power electronic packaging.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0011] The present invention provides a method for preparing copper nanowires for packaging interconnects. By comprehensively controlling the ratio of copper source, surface coating agent and reducing agent, reaction time and temperature, copper nanowires with diameters of 20-300 nm and lengths of 1-60 μm are obtained. In the field of power electronics packaging, due to the low temperature resistance of chips, the packaging temperature cannot exceed 250℃. However, nanowires in the 20-300 nm diameter range have a low melting point effect, which can melt at temperatures far below the melting point to achieve packaging interconnects between different interfaces, meeting the packaging requirements of no more than 250℃. At the same time, the micron-scale wire length is very advantageous for the preparation of copper nanowires. The overlapping of long wires is conducive to the formation of copper films, while wires that are too short are very unfavorable for the formation of copper films. Secondly, the preparation method has a wide process window between raw materials and is a one-time sample addition method. It has no requirements on the sample addition speed and order, making the operation convenient and fast. It is not sensitive to the reaction liquid volume and can be mass-produced. The prepared copper nanowires have controllable and adjustable thickness, simple process, good batch stability, certain mechanical strength, and can be sintered at low temperatures. In addition, this preparation method has a high yield; 10L of reaction solution can produce 40-80g of copper nanowires. Attached Figure Description
[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0013] Figure 1 This is a macroscopic photograph of the copper nanowire mother liquor in Example 1;
[0014] Figure 2 This is a macroscopic photograph of the nano-copper film in Example 1;
[0015] Figure 3 This is a low-magnification SEM micrograph of the nano-copper film in Example 1;
[0016] Figure 4 This is a high-magnification SEM micrograph of the nano-copper film in Example 1;
[0017] Figure 5 EDS image of the nano-copper film in Example 1;
[0018] Figure 6 The elemental spectrum of the nano-copper film in Example 1 is shown.
[0019] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.
[0022] Unless otherwise specified, all medicines / reagents used are commercially available.
[0023] This invention proposes a method for preparing a nano-copper film for encapsulation interconnection, characterized by comprising the following steps:
[0024] S1: Add copper source, surface coating agent, reducing agent, and deionized water to a pressure-resistant, temperature-resistant, and sealable container. The molar ratio of copper source, surface coating agent, and reducing agent is 1:(2-10):(0.2-5). Stir in an oil bath at 60-120°C until a uniform blue suspension is formed. Turn off the stirring, then raise the oil bath temperature to 120-180°C and react at 120-180°C for 3-10 hours. When the reaction solution turns reddish-brown, turn off the heating and cool to room temperature to obtain copper nanowire mother liquor.
[0025] S2: Add solvent and stir at 40-80℃ for 0.1-1h to obtain copper nanowire dilution solution.
[0026] S3: The copper nanowire dilution solution is added to the papermaking equipment. After solid-liquid separation under positive and negative pressure, the solution is rinsed and then vacuum dried to obtain a copper nanofilm.
[0027] The preparation method provided by this invention has the following significant advantages compared with the prior art:
[0028] (1) Cost advantage: The raw material cost is low. The raw material cost of nano silver is about 15 to 30 times that of nano copper. The preparation and washing cost of copper nanowires is low. They can be prepared in an open oil bath using pressure-resistant bottles and other high-pressure and high-temperature sealed containers. The reaction process can be monitored in real time. Copper nanowires are in the micrometer range in length, resulting in high yield and simple washing. Copper nanowire washing does not require the use of a single high-cost solvent. Instead, a small amount of various acid and alkali solutions, organic solvents, and deionized water are mixed to remove the coating on the surface of copper nanowires.
[0029] (2) Advantages of the preparation process: The reduction rate of silver ions and the growth rate of elemental silver in the preparation of silver nanowires are very sensitive to the reaction temperature and the concentration of silver source. Therefore, the amount of silver source added, the addition rate, and the temperature field distribution of the reaction solution during addition must be strictly controlled, otherwise the batch stability of silver nanowires will be seriously affected. Copper nanowires are prepared by hydrothermal reaction, which has a wide process window between raw materials and is a one-time addition. There are no requirements for the addition rate, the order of raw material addition, and the reaction volume. The operation is convenient and quick, and it can be mass-produced. The nano-copper film can be prepared by removing the surface coating agent with a suitable solvent and then using papermaking equipment. The preparation method is simple and quick and has good batch stability.
[0030] (3) Advantages of encapsulation interconnection: Nano silver paste requires dispensing and is only suitable for encapsulating small-sized devices. In addition, the organic components in the silver paste affect the performance. Imported nano silver film is very thin and brittle and cannot be manually transferred. It requires a two-step encapsulation process of transfer and hot pressing. It is only suitable for encapsulation interconnection between chips and substrates and is not suitable for encapsulation interconnection between ultra-large (≥30mm) substrates and heat sinks. Nano copper film is a structure of copper nanowires overlapping each other. It has high strength, can be mechanically cut and manually transferred. The encapsulation interconnection process is simple and the thickness is controllable and adjustable. It is widely applicable to the size of encapsulated devices.
[0031] Preferably, in step S1, the pressure during the reaction at 120–180°C is 0.05–0.3 MPa.
[0032] The synthesis temperature range for copper nanowires is 120–180℃. If the reaction vessel is not sealed, the reaction solution boils violently within this temperature range, the deionized water in the reaction solution is rapidly depleted, the reaction process becomes uncontrollable, and the nanoproduct cannot be obtained. During the reaction, the pressure in the pressure vessel is approximately 0.05–0.3 MPa. Within this pressure range, the reaction solution does not boil, the reaction is mild and controllable, and the reaction product is copper nanowires.
[0033] Preferably, in step S1, the copper source is a copper-containing inorganic salt, specifically one of CuCl2, CuCl2·2H2O, CuSO4·5H2O, Cu(NO3)2, and Cu(NO3)2·3H2O.
[0034] Preferably, in step S1, the surface coating agent is an aliphatic amine.
[0035] Preferably, the aliphatic amine is at least one of diethylenediamine, octadeceneamine, stearylamine, hexadecyltrimethylammonium chloride, and hexamethylenediamine.
[0036] Preferably, in step S1, the reducing agent is at least one of glucose, ascorbic acid, hydrazine hydrate, formaldehyde, and ammonia.
[0037] Preferably, in step S1, the copper nanowires in the copper nanowire mother liquor have a diameter of 20-300 nm and a length of 1-60 μm.
[0038] Preferably, in step S2, the solvent is at least two of the following: low-boiling-point alcoholic organic solvents, acidic solutions, alkaline solutions, low-boiling-point etheric organic solvents, water-soluble dispersants, and deionized water. Specifically, it is a compound solution of at least two of the following: low-boiling-point alcoholic organic solvents such as ethanol and isopropanol; acidic solutions such as acetic acid and hydrochloric acid; alkaline solutions such as ammonia and NaOH; low-boiling-point etheric organic solvents; water-soluble dispersants such as polyvinylpyrrolidone (PVP) and hydroxycellulose; and deionized water.
[0039] The volume of the solvent added is 2 to 10 times the volume of the copper nanowire mother liquor.
[0040] Preferably, in step S3, the solvent used for rinsing includes at least one of an acid solution and an alkaline solution, and further includes at least one of a low-boiling-point alcohol organic solvent, a low-boiling-point ether organic solvent, a water-soluble dispersant, and deionized water.
[0041] Aliphatic amine surface coating agents are insoluble in water and have a strong adsorption effect on nanowires. The content of the surface coating agent has a great influence on the strength and service reliability of the nano-copper film encapsulation interconnect. Adding acid or alkali to the rinsing agent can effectively remove the amine coating agent on the surface of the nano-copper wire.
[0042] The rinsing process is carried out at a temperature of 40–80°C and involves 2–10 rinsing cycles.
[0043] Preferably, in step S3, the negative pressure of the positive and negative pressure is 0.01 to 0.1 MPa, and the positive pressure is 0.1 to 0.5 MPa.
[0044] This invention also proposes a nano-copper film for encapsulation interconnection, prepared by the method described above; the nano-copper film has a thickness of 20–300 μm and an areal density of 40–500 g / m³. 2 The impurity content is less than 1%.
[0045] This invention also proposes an application of a nano-copper film for packaging interconnection, using the nano-copper film prepared by the above-described preparation method or the above-described nano-copper film as a thermal interface material in the field of power electronics packaging, for packaging interconnection between chips, metal plates, metal-ceramic composite plates, and heat sinks.
[0046] Example 1
[0047] This embodiment provides a copper nanofilm for encapsulation interconnection, the copper nanofilm having a thickness of 90 μm and an areal density of 180 g / m³. 2 The content of impurities such as organic matter is 0.97%.
[0048] This embodiment provides a method for preparing the nano-copper film for encapsulation interconnection, including the following steps:
[0049] CuCl2, diethylenediamine, glucose (molar ratio 1:5:0.4), and 3 L H2O were added simultaneously to a pressure-resistant flask. The mixture was stirred in a 60°C oil bath for 0.5 h until a uniform blue suspension formed. The stirring was then stopped, the pressure-resistant flask was sealed, and the reaction temperature was increased to 120°C for 6 h. When the reaction solution turned brownish-red, the heating was stopped, and the mixture was cooled to room temperature to obtain the copper nanowire mother liquor. The macroscopic morphology of this mother liquor is shown below. Figure 1 As shown in the figure (the mother liquor is uniformly viscous without stratification and is brownish-red in color); 1 wt% acetic acid, 1.1 wt% ethanol, and deionized water were mixed evenly and added to the copper nanowire mother liquor at a volume 5 times that of the mother liquor. The purification process was 80℃ / 50rpm / 0.5h. After cooling the purified dispersion to room temperature, it was added to a paper machine. After solid-liquid separation under 0.1MPa negative pressure and 0.3MPa positive pressure, the mixture was washed with 5 wt% NaOH solution, deionized water, and ethanol at 60℃ / 2 times, followed by vacuum drying at 60℃ / 5min to obtain the nano-copper film. Its macroscopic and microscopic morphology are shown in the figure. Figures 2-4 As shown, the silver film surface exhibits a uniform brownish-red color. Measurements indicate that the copper nanowires have a diameter of 40–80 nm and a length of 30–60 μm. Their elemental spectra and elemental distribution are as follows: Figure 5 , 6 As shown, the nano-copper film mainly contains C and Cu elements. Cu is the main component of the nano-copper film, which is copper nanowires, while C is the impurity on the surface of the copper nanowires, with a content of less than 1%.
[0050] Example 2
[0051] This embodiment provides a copper nanofilm for encapsulation interconnection. The copper nanofilm has a thickness of 200 μm and an areal density of 350 g / m³. 2 The content of impurities such as organic matter is 0.92%.
[0052] This embodiment provides a method for preparing the nano-copper film for encapsulation interconnection, including the following steps:
[0053] Cu(NO3)2, stearylamine, ascorbic acid, and 5 L H2O were added to a pressure-resistant bottle in a molar ratio of 1:4:0.3. The mixture was stirred in a 100°C oil bath for 2 hours until the raw material formed a uniform blue suspension. The stirring was then stopped, the pressure-resistant bottle was sealed, and the reaction temperature was increased to 160°C for 6 hours. When the reaction solution turned brownish-red, the heating was stopped, and the mixture was cooled to room temperature to obtain a copper nanowire mother liquor. The diameter of the copper nanowires was approximately 110-160 nm, and the length was approximately 15-40 μm. 0.8 wt... After uniformly mixing 1% formic acid, 1wt% ethanol, 1.2wt% sulfated castor oil, and deionized water, the mixture was added to the copper nanowire mother liquor at a volume 8 times that of the mother liquor. The purification process was carried out at 80℃ / 200rpm / 1h. After cooling the purified dispersion to room temperature, it was added to a paper machine. After solid-liquid separation under a negative pressure of 0.05MPa and a positive pressure of 0.2MPa, the mixture was washed with acetic acid solution, deionized water, and ethanol at 60℃ / 2 times and vacuum dried at 50℃ / 10min to obtain the copper nanofilm.
[0054] Example 3
[0055] This embodiment provides a copper nanofilm for encapsulation interconnection, the copper nanofilm having a thickness of 70 μm and an areal density of 150 g / m³. 2 The content of impurities such as organic matter is 0.95%.
[0056] This embodiment provides a method for preparing the nano-copper film for encapsulation interconnection, including the following steps:
[0057] Cu(NO3)2, octadeceneamine, glucose in a molar ratio of 1:8:4, and 2 L H2O were added to a stainless steel reactor in one step. The mixture was stirred in an oil bath at 120°C for 2 hours until a uniform blue suspension was formed. The stirring was then stopped, the reactor was sealed, and the reaction temperature was increased to 150°C for 3 hours. When the reaction solution turned brownish-red, the heating was stopped, and the mixture was cooled to room temperature to obtain a copper nanowire mother liquor. The copper nanowires had a diameter of approximately 30-70 nm and a length of approximately 1-6 μm. 0.6 w After mixing 1% acetic acid, 1 wt% polyvinylpyrrolidone, and deionized water evenly, the mixture was added to the copper nanowire mother liquor at a volume 10 times that of the mother liquor. The purification process was carried out at 80℃ / 150rpm / 0.5h. After cooling the purified dispersion to room temperature, it was added to a paper machine. After solid-liquid separation under a negative pressure of 0.05MPa and a positive pressure of 0.3MPa, the mixture was washed with ammonia solution, deionized water, and ethanol at 60℃ / 2 times and vacuum dried at 50℃ / 10min to obtain the copper nanofilm.
[0058] Comparative Example 1
[0059] This embodiment provides a method for preparing a nano-copper film for encapsulation interconnection, including the following steps:
[0060] CuCl2, octadeceneamine, hydrazine hydrate in a molar ratio of 1:1:0.2, and 2 L H2O were added to a pressure-resistant bottle at once. The mixture was stirred in an oil bath at 100 °C for 2 hours until the raw materials formed a uniform blue suspension. The stirring was then stopped, the pressure-resistant bottle was sealed, and the reaction temperature was increased to 160 °C for 1 hour. The reaction solution was in a layered state, with a greenish-white suspended solid on top and a light blue clear liquid on the bottom. The reaction temperature was extended to 6 hours, but the state of the reaction solution remained unchanged and it was still in a layered state. Reddish-brown copper was not obtained. In this state, the copper salt was not reduced to copper and still existed in the form of a compound. The reaction failed.
[0061] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention's specification and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for preparing a nano-copper film for encapsulation interconnection, characterized in that, Includes the following steps: S1: Add copper source, surface coating agent, reducing agent, and deionized water to a high-pressure, high-temperature, and sealable container. The molar ratio of copper source, surface coating agent, and reducing agent is 1:(2~10):(0.2~5). Stir in an oil bath at 60~120℃ until a uniform blue suspension is formed. Turn off the stirring, then raise the oil bath temperature to 120~180℃ and react at 120~180℃ and a pressure of 0.05-0.3MPa for 3~10 hours. When the reaction solution turns reddish-brown, turn off the heating and cool to room temperature to obtain copper nanowire mother liquor. S2: Add solvent and stir at 40~80℃ for 0.1~1h to obtain copper nanowire dilution solution; S3: The copper nanowire dilution solution is added to the papermaking equipment. After solid-liquid separation under positive and negative pressure, the solution is rinsed and then vacuum dried to obtain a copper nanofilm. In step S1, the copper source is a copper-containing inorganic salt, which is one of CuCl2, CuCl2·2H2O, CuSO4·5H2O, Cu(NO3)2 and Cu(NO3)2·3H2O. In step S3, the negative pressure of the positive and negative pressure is 0.01 to 0.1 MPa, and the positive pressure is 0.1 to 0.5 MPa; In step S3, the solvent used for rinsing includes at least one of acidic solutions and alkaline solutions, and also includes at least one of low-boiling-point alcoholic organic solvents, low-boiling-point etheric organic solvents, water-soluble dispersants, and deionized water. The rinsing temperature is 40-80°C, and the number of rinsing cycles is 2-10. In step S1, the surface coating agent is an aliphatic amine, and the copper nanowires in the copper nanowire mother liquor have a diameter of 20~300nm and a length of 1~60μm.
2. The preparation method according to claim 1, characterized in that, The aliphatic amine is at least one of diethylenediamine, octadeceneamine, stearylamine, hexadecyltrimethylammonium chloride, and hexamethylenediamine.
3. The preparation method according to claim 1, characterized in that, In step S1, the reducing agent is at least one of glucose, ascorbic acid, hydrazine hydrate, formaldehyde, and ammonia.
4. The preparation method according to claim 1, characterized in that, In step S2, the solvent is at least two of the following: low-boiling-point alcohol organic solvents, acid solutions, alkaline solutions, low-boiling-point ether organic solvents, water-soluble dispersants, and deionized water.
5. A nano-copper film for encapsulating interconnects, characterized in that, The nano-copper film is prepared by the preparation method according to any one of claims 1 to 4; the thickness of the nano-copper film is 20 to 300 μm, and the areal density is 40 to 500 g / m³. 2 The impurity content is less than 1%.
6. An application of a nano-copper film for encapsulation interconnection, characterized in that, The nano-copper film prepared by any one of claims 1 to 4 or the nano-copper film of claim 5 is used as a thermal interface material in the field of power electronic packaging.
